The problem of training masters of chemical direction of pedagogical education (Pedagogy of Higher and Secondary Education, 2021)
The article is sanctified to the problems of educating of students after an educational-qualifying level master's degree in pedagogical higher educational establishments. The charts of realization of requirements of society are offered to the level of preparation in a city council on the base of intellectually-emotional aspect during teaching of desciplines of chemical cycle.
Keywords: master's degree; intellectually-emotional culture; problems of professional preparation after a master's degree; pedagogical education